STUDI KARAKTERISTIK MINERAL MATTER DAN PENGARUHNYA TERHADAP KUALITAS BATUBARA DAERAH TONDONGKURAH KABUPATEN PANGKEP SULAWESI SELATAN - SUFRIADIN
Abstract : The mineralogical study of three coal samples from Tondongkurah, South Sulawesi have been carried out with using X-ray diffraction and petrographic methods in order to determine minerals distribution on density fractions which related to their quality. Heavy liquid was applied with density in the range of 1.2 to t7 gr/ml. Kaolinite dominate mineral proportion in the coal samples followed by illite and mixed layer illite-smectite. Some other minerals like quartz, calcite, pyrite, and anatase, are also present. Clay minerals quantitavely have great contribution to its ash formation. The high content of Fe2O3 in ash, probably occurs as organometallic compound. Regression analysis shows that, there are strongly correlation between minerals distribution and relative density ( r = 0.9805), whereas relationship between minerals distribution and calorific value is strongly liniear negative ( r = - 0.9455 ). The result of washability test, theoretically indicate that Tondongkurah coal is difficult to wash by using a medium with relative density up to 1.5 grim!. Even though at such density can be recovered 85.82 % of coal yield, but the ash yield are still more than 10 %. Totally sulfur analysis for each relative density fractions exhibit that reduction of sulfur content is not effective due to its element attached to organic complexes in coal structure so that it could not be physically removed.